"Released”, yet not free: an overview of the parole (system) in the city of São Paulo - Viviane Balbuglio (Revista Brasileira de Direito Processual Penal, 2021)
Using the methodology of participant observation and documentary analysis of provisions and court documents related to the execution of penalties outside prisons in the state of São Paulo, this article aims to develop descriptions and reflections on the parole and the practice of periodic mandatory court appearance. Starting with the contextualization of the regimes/mechanisms that render invisible the parole as a type of penalty, the article presents some aspects of the judicial organization for the enforcement of court decisions in the state of São Paulo and it also describes events (scenes) and elements of the mandatory court appearance in two different sectors of the criminal court of Barra Funda, located in the city of São Paulo – the biggest criminal courthouse in Latin America.